A Compositional Statistical Analysis of Global Capital Stock - Larrosa, Juan Manuel Ceferino (2014)
What has been the pattern of capital composition associated with World economies? We make an exploratory statistical analysis based on compositional data transformed by Aitchison log ratios for measuring statistical association among the components. The goal is to detect distinctive patterns in the composition. As initial findings could be cited that: 1) Sectorial components behaved in a correlated way, building industries on one side and, in a less clear view, equipment industries on the other. 2) Full sample estimation shows a negative correlation between durable goods component and other-buildings component and between transportation and building industries components.